Pemanfaatan Plasma Nutfah Mikroba Bordetella bronchiseptica sebagai Perangkat Deteksi Antibodi - Siti Chotiah (Buletin Plasma Nutfah, 2008)
Microbe germplasm of Bordetella bronchiseptica has been found in pigs in Indonesia and recognized as the causal agent of atrophic rhinitis and pneumonia, and also one of the agents involved in porcine respiratory disease complex. Those microbes have been characterized and conserved ex situ at Balitvet Culture Collection. The aim of this research was to find out seroepidemiological of B. bronchiseptica infections at four pig herds in two regencies in Central Java, by utilizing the germ plasma as antibody detection kit. The ELISA technique used lypopolysaccharide and sera hypperimmune of B. bronchiseptica local isolate as an antigen and positive sera respectively. Referring to cut off level of 0.404, the survey results showed that of 25.4% of 63 pig serum samples examine by ELISA were positively infected by B. bronchiseptica; 14.29% and 11, 11% from Karanganyar regencies and Sragen regencies respectively. Base on pig ages it showed that 10.35%, 24%, and 77.8% to be seropositive from less than three-month age group, three-month until five-month age group, and more than five-month age group respectively. Base on pig farm it was showed that 28.60; 30; 13.64; and 40% were seropositive collected from Farm 1, Farm 2, Farm 3 and Farm 4 respectively. The results indicated that B. bronchiseptica infection was spread on four pig herds in two regencies in Central Java with the higest seropositive (77,8%) in more than five-month age group. AbstrakPlasma nutfah Bordetella bronchiseptica telah ditemukan pada babi di Indonesia, selain merupakan agen penyebab atrophic rhinitis dan pneumoni juga salah satu agen porcine respiratory disease complex. Mikroba tersebut telah dikarakterisasi dan dikonservasi ex situ di Balitvet Culture Collection (BCC). Tujuan penelitian adalah untuk mengetahui seroepidemiologi infeksi B. bronchiseptica pada empat peternakan babi di dua kabupaten di Jawa Tengah, dengan memanfaatkan plasma nutfah tersebut sebagai bahan baku perangkat deteksi antibodi. Teknik Enzyme-linked Immunosorbent Assay (ELISA) menggunakan lypopolysaccharide dan serum imun dari isolat lokal B. bronchiseptica BS(BCC 2455) masing-masing sebagai antigen dan serum kontrol positif. Mengacu pada nilai cut off 0,404, hasil survei menunjukkan bahwa 25,4% dari 63 sampel serum yang diperiksa positif terinfeksi oleh B. bronchiseptica, 14,3% di antaranya berasal dari Kabupaten Karanganyar dan 11,1% dari Kabupaten Sragen. Berdasarkan pengelompokan umur diketahui bahwa seropositif sebanyak 10,35; 24; dan 77,8% masing-masing berasal dari kelompok umur di bawah 3 bulan, kelompok umur 3 sampai 5 bulan, dan kelompok umur di atas 5 bulan. Berdasarkan peternak sebaran seropositif sebanyak 28,60; 30; 13,64; dan 40% masing-masing pada peternakan 1, 2, 3, dan 4. Hal ini menunjukkan infeksi B. bronchiseptica telah tersebar di empat peternakan babi di dua kabupaten di Jawa Tengah dengan seropositif tertinggi (77,8%) pada kelompok babi umur di atas 5 bulan.